Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{2}{3}:0.1x=\dfrac{4}{3}:0.8=\dfrac{4}{3}:\dfrac{4}{5}=\dfrac{5}{3}\)
=>0,1x=2/3:5/3=2/5
=>x=1/10:2/5=1/10x5/2=5/20=1/4
\(\dfrac{4}{3}:0,8=\)\(\dfrac{2}{3}:0,1x\)
\(\dfrac{4}{3}:\dfrac{4}{5}=\dfrac{2}{3}\)\(:\dfrac{1}{10}x\)
\(\dfrac{4}{3}.\dfrac{5}{4}=\dfrac{2}{3}:\dfrac{x}{10}\)
\(\dfrac{5}{3}=\dfrac{2}{3}.\dfrac{10}{x}\)
⇒\(\dfrac{10}{x}=\dfrac{5}{3}:\dfrac{2}{3}\)\(=\dfrac{5}{3}.\dfrac{3}{2}\)\(=\dfrac{5}{2}\)
⇒\(\dfrac{10}{x}=\dfrac{5}{2}\)⇒\(x=10:\dfrac{5}{2}=10.\dfrac{2}{5}=\dfrac{20}{5}=4\)
\(\frac{4}{3}:0,8=\frac{2}{3}:0,1x\\ \Leftrightarrow x=\frac{4}{3}:0,8:\frac{2}{3}.0,1=\frac{4}{3}:\frac{4}{5}:\frac{2}{3}.\frac{1}{10}\\ \Leftrightarrow x=\frac{4}{3}.\frac{5}{4}.\frac{3}{2}.\frac{1}{10}=\frac{5}{20}=\frac{1}{4}\)
\(1\dfrac{1}{3}:0,8=\dfrac{2}{3}:\left(0,1\right).x\)
\(\Rightarrow\dfrac{4}{3}:\dfrac{4}{5}=\dfrac{2}{3}:\dfrac{1}{10}.x\)
\(\Rightarrow\dfrac{4}{3}.\dfrac{5}{4}=\dfrac{2}{3}.10x\)
\(\Rightarrow\dfrac{5}{3}=\dfrac{2}{3}.10x\)
\(\Rightarrow10x=\dfrac{5}{3}:\dfrac{2}{3}\)
\(\Rightarrow10x=\dfrac{5}{2}\)
\(\Rightarrow x=\dfrac{5}{2}:10=\dfrac{1}{4}\)
Vậy \(x=\dfrac{1}{4}\)
\(1\dfrac{1}{3}:0,8=\dfrac{2}{3}:0,1x\Rightarrow\dfrac{4}{3}:\dfrac{3}{5}=\dfrac{2}{3}:\dfrac{1}{10}x\)
\(\Rightarrow\dfrac{4}{3}.\dfrac{5}{3}=\dfrac{2}{3}.10x\Rightarrow\dfrac{20}{9}=\dfrac{20}{3}x\Rightarrow x=\dfrac{1}{3}\)
Vậy...................................................
a)\(-\frac{3}{7}+x=\frac{1}{3}\)
\(x=\frac{1}{3}+\frac{3}{7}\)
\(x=\frac{16}{21}\)
b)\(\frac{3}{4}+\frac{1}{4}:x=\frac{2}{5}\)
\(\frac{1}{4}:x=\frac{2}{5}-\frac{3}{4}\)
\(\frac{1}{4}:x=-\frac{7}{20}\)
\(x=\frac{-7}{20}x\frac{1}{4}\)
\(x=-\frac{7}{80}\)
d)\(\left|x-3\right|=\frac{1}{2}\)
\(\Rightarrow\hept{\begin{cases}x-3=\frac{1}{2}\\x-3=\frac{-1}{2}\end{cases}}\Rightarrow\hept{\begin{cases}x=\frac{7}{2}\\x=\frac{5}{2}\end{cases}}\)
Mk bổ sung nha
c)\(1\frac{1}{3}:0,8=\frac{2}{3}:0,1x\)
\(\frac{5}{3}=\frac{2}{3}:0,1x\)
\(0,1x=\frac{2}{3}:\frac{5}{3}\)
\(0,1x=\frac{2}{5}\)
\(x=\frac{2}{5}:0,1\)
\(x=4\)
\(\left(1+\frac{2}{3}-\frac{1}{4}\right)\left(0.8-\frac{3}{4}\right)^2\)
= \(\left(\frac{12+8-3}{12}\right)\left(\frac{3,2-3}{4}\right)^2\)
= \(\frac{17}{12}.\left(\frac{0,2}{4}\right)^2\)
\(\frac{17}{12}.\frac{1}{400}\)
=\(\frac{17}{4800}\)
\(\left(1+\frac{2}{3}-\frac{1}{4}\right)\left(0,8-\frac{3}{4}\right)^2\)
\(=\left(\frac{12}{12}+\frac{8}{12}-\frac{3}{12}\right)\left(\frac{4}{5}-\frac{3}{4}\right)^2\)
\(=\frac{17}{12}\cdot\left(\frac{16}{20}-\frac{15}{20}\right)^2\)
\(=\frac{17}{12}\cdot\left(\frac{1}{20}\right)^2\)
\(=\frac{17}{12}\cdot\frac{1}{400}\)
\(=\frac{17}{4800}\)
\(\frac{4}{3}\div0,8=\frac{2}{3}\div0,1\)
\(\frac{5}{3}\ne\frac{20}{3}\)
\(\Rightarrow\frac{4}{3}\div0,8\ne\frac{2}{3}\div0,1\)